f(x) = 3x^2 cos(x)cot(x)

Differentiate:

6x(cosx)(cotx) + (-sinx)(3x^2)(cotx) + (-csc^2x)(3x^2)(cosx)

Is this the completely wrong way to go about this problem?

Printable View

- Jul 14th 2011, 12:45 AMNeoSonataDifferentiate f(x) = (3x^2) ( cosx)(cotx)
*f*(*x*) = 3x^2 cos(*x*)cot(*x*)

Differentiate:

6x(cosx)(cotx) + (-sinx)(3x^2)(cotx) + (-csc^2x)(3x^2)(cosx)

Is this the completely wrong way to go about this problem? - Jul 14th 2011, 12:50 AMFernandoRevillaRe: Differentiate f(x) = (3x^2) ( cosx)(cotx)